Modified vitamin B6 microbiological assay for basal ingredients of dry mix effervescent beverages - Manaois, Abigail C.
ABSTRACT This study aimed to assess vitamin B6 recovery in basal ingredients of dry mix effervescent drinks using an adapted microbiological assay based on a method described by Association of Vitamin Chemists (1966). Modifications in the method were done in the inoculum preparation, sample preparation, and basal medium of the method to improve the percent recovery of the vitamin in the samples. A survey conducted on seven locally sold dry mix energy drinks identified sodium bicarbonate, citric acid, and maltodextrin as widely used basal ingredients in effervescent formulations. These ingredients were used as carrier samples for vitamin B6 in the test microbiological assays. The unmodified microbiological assay gave inconclusive results in quantifying the vitamin B6 due to the lack of trend in the yeast growth in the standard assay solutions. Modifications were carried out to improve the growth pattern by increasing the S. carlsbergensis inoculum concentration from 0.1 mg/ml to 1 mg/ml which required the addition of a washing and pelletizing step to prepare the yeast suspension resulting to 10% vitamin recovery in sodium bicarbonate-citric acid but not in maltodextrin. The sample preparation was then modified to a simple acid dissolution which eliminated the autoclaving and pH adjustment steps, resulting to a 20% vitamin recovery for both the acid-alkali and maltodextrin samples. The final modification was the substitution of the basal medium with Sabouraud's broth as a simpler growth media which is commercially available. Results of the basal modification showed a marked increase of 83% vitamin recovery for the acid-alkali but not for maltodextrin. The consolidated modifications showed a 67-113% vitamin recovery for the sodium bicarbonate-citric acid sample with 3, 4, 5% vitamin B6 (w/w). This modified microbiological assay for vitamin B6 has potential application for beverages comprising mainly of alkali-acid effervescent components such as energy drinks. Furthermore, the method can be used as a tool for in-process monitoring of vitamin B6 in acidic medium which would eventually be incorporated with carbohydrates and other ingredients in beverage formulations.